2018
DOI: 10.2139/ssrn.3287176
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Management with Cryptocurrencies: The Role of Estimation Risk

Abstract: This paper contributes to the literature on cryptocurrencies, portfolio management and estimation risk by comparing the performance of naïve diversification, Markowitz diversification and the advanced Black-Litterman model with VBCs that controls for estimation errors in a portfolio of cryptocurrencies. We show that the advanced Black-Litterman model with VBCs yields superior out-of-sample risk-adjusted returns as well as lower risks. Our results are robust to the inclusion of transaction costs and short-selli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
2
31
0
1
Order By: Relevance
“…In the literature, many studies have investigated the performance of cryptocurrency inclusive portfolios ( Platanakis et al., 2018 ; Platanakis and Urquhart, 2019 ; Borri, 2019 ; Liu, 2019 ; Brauneis and Mestel, 2019 ). Most of these studies have discussed the portfolio diversification using only Bitcoin as a benchmark.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, many studies have investigated the performance of cryptocurrency inclusive portfolios ( Platanakis et al., 2018 ; Platanakis and Urquhart, 2019 ; Borri, 2019 ; Liu, 2019 ; Brauneis and Mestel, 2019 ). Most of these studies have discussed the portfolio diversification using only Bitcoin as a benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…Symitsi and Chalvatzis provided an extensive analysis of the economic value of Bitcoin and suggested that the decrease in the portfolio risk comes from the low correlations between the assets and Bitcoin. Also, further contributing to the literature, Platanakis and Urquhart highlighted that, given the higher potential estimation error in a portfolio of cryptocurrencies, the portfolio theory might face significant difficulties ( Platanakis and Urquhart, 2019 ). In another research study, Liu, (2019 ) analyzed the results of portfolio diversification on six different portfolios of the ten cryptocurrencies taken into account and found that the Naïve Portfolio performed better than all the other portfolios when calculating the return and risk profile using the Sharpe ratio.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Scala et al (2019) adopted the Markowitz framework to propose a simplified strategy in managing portfolios of renewable energy sources. Similarly, Platanakis and Urquhart (2019) analyzed the effect of including cryptocurrencies, and found the Markowitz model to rank second after the Black-Litterman model. Platanakis et al (2018) also found there is very little difference when choosing between an equally weighted portfolio and the optimal mean-variance portfolio.…”
Section: Modern Portfolio Theorymentioning
confidence: 99%
“…Two related topics have emerged in the literature: (a) Bitcoin's diversification potential (Liu, 2018;Platanakis and Urquhart, 2019;Aslanidis et al, 2019); (b) daily seasonality in Bitcoin markets (Mbanga, 2019;Ma and Tanizaki, 2019;Caporale and Plastun, 2019;Aharon and Qadan, 2019). Considering the growing interest of the financial industry to provide cryptocurrency related products, such as exchange traded funds, mutual or hybrid funds, we consider that it is relevant to address both issues together.…”
Section: Introductionmentioning
confidence: 99%